2011
DOI: 10.5039/agraria.v6i4a1257
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Ca2+ externo no conteúdo de Na+ e K+ em cajueiros expostos a salinidade

Abstract: Objetivando avaliar o efeito do Ca 2+ externo na absorção e transporte de Na + e K + em plântulas de cajueiro anão precoce, expostas a altos níveis de NaCl, sementes do clone de cajueiro, CCP 06, foram germinadas e cultivadas em vermiculita dentro de casa de vegetação. Plântulas com aproximadamente 8 folhas foram transferidas para condições controladas de temperatura a 25±2 °C, U.R 80%, fotoperíodo de 12 h e 240 μmol m-2 s-1 , onde elas foram divididas em dois ensaios. No primeiro as raízes foram destacadas da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
1
19
0
3
Order By: Relevance
“…According to Alves et al (2011) one of the mechanisms of resistance to excess of Na + in plants is to maintain adequate potassium nutrition in plant tissues, which occurred in the present work, where K + contents were above the critical level. The selectivity of the root system for K + over Na + should be sufficient to satisfy K + contents required for the metabolic processes, ion transport regulation and osmotic adjustment (Munns & Tester, 2008).…”
Section: Levels Of Namentioning
confidence: 60%
See 4 more Smart Citations
“…According to Alves et al (2011) one of the mechanisms of resistance to excess of Na + in plants is to maintain adequate potassium nutrition in plant tissues, which occurred in the present work, where K + contents were above the critical level. The selectivity of the root system for K + over Na + should be sufficient to satisfy K + contents required for the metabolic processes, ion transport regulation and osmotic adjustment (Munns & Tester, 2008).…”
Section: Levels Of Namentioning
confidence: 60%
“…This fact explains the Na + accumulation in roots as it can be observed in several studies (Lacerda et al, 2004, Alves et al, 2011Krishnasamy et al, 2014). Krishnasamy et al (2014) found a reduction in the K + /Na + ratio in wheat plants of different cultivars when Na + was added in the soil.…”
Section: Levels Of Namentioning
confidence: 63%
See 3 more Smart Citations